2017
DOI: 10.21826/2446-8231201772107
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura da comunidade de liquens corticícolas em área urbana e rural no município de Novo Hamburgo, Rio Grande do Sul, Brasil

Abstract: RESUMO -O objetivo do estudo foi analisar a composição e estrutura da comunidade de liquens foliosos e fruticosos corticícolas em área urbana e rural do município de Novo Hamburgo, RS. Foram analisados dez forófi tos em cada área e o mapeamento das espécies realizado pelo método do acetato. Foram analisados os parâmetros: riqueza, frequência, cobertura e valor de importância em cada área. No total foram identifi cadas 55 espécies para as duas áreas. A riqueza foi similar entre as áreas: urbana (33) e rural (32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Studies with vascular epiphytes in the HBSR area have verified changes in richness and diversity of the riparian forest sites in different matrices and have emphasized the importance of their conservation and preservation (Rocha-Uriartt et al 2016). In this study, we found that the preservation actions associated with agropastoral practices were decisive for the conservation of habitats, such as in the S4 forest site of the rural-urban matrix, in which rare species were found, including Herpothallon pustulatum (crustose) and the genera Ricasolia and Sticta, which are known to occur in more preserved environments (Käffer & Martins 2014;López et al 2016;Lehnen et al 2017).…”
Section: Discussionmentioning
confidence: 79%
“…Studies with vascular epiphytes in the HBSR area have verified changes in richness and diversity of the riparian forest sites in different matrices and have emphasized the importance of their conservation and preservation (Rocha-Uriartt et al 2016). In this study, we found that the preservation actions associated with agropastoral practices were decisive for the conservation of habitats, such as in the S4 forest site of the rural-urban matrix, in which rare species were found, including Herpothallon pustulatum (crustose) and the genera Ricasolia and Sticta, which are known to occur in more preserved environments (Käffer & Martins 2014;López et al 2016;Lehnen et al 2017).…”
Section: Discussionmentioning
confidence: 79%
“…In the present study, yet another new genus, Emmanuelia, is erected to accommodate a group of lobarioid lichens that cannot be placed in any of the existing genera. The species of interest belong to a lineage mostly restricted to the Neotropics and the southeastern United States, and were previously treated as members of the genus Lobaria and subsequently considered part of Ricasolia (Moncada et al 2013;Käffer et al 2016;Lehnen et al 2017;Etayo et al 2018). Yoshimura (1998) treated the South American taxa as L. quercizans group, also implying a close relationship to Ricasolia.…”
Section: Introductionmentioning
confidence: 99%